Toward emulating nuclear reactions using eigenvector continuation - C. Drischler (Elsevier, 2021)
We construct an efficient emulator for two-body scattering observables using the general (complex) Kohn variational principle and trial wave functions derived from eigenvector continuation. The emulator simultaneously evaluates an array of Kohn variational principles associated with different boundary conditions, which allows for the detection and removal of spurious singularities known as Kohn anomalies. When applied to the K-matrix only, our emulator resembles the one constructed by Furnstahl et al. (2020) [29] although with reduced numerical noise. After a few applications to real potentials, we emulate differential cross sections for 40Ca(n,n) scattering based on a realistic optical potential and quantify the model uncertainties using Bayesian methods. These calculations serve as a proof of principle for future studies aimed at improving optical models.